QUALITY ANALYSIS OF ADMINISTRATIVE AND MEDICAL SERVICES AT ROYAL PROGRESS INTERNATIONAL JAKARTA INTERNATIONAL HOSPITAL IN THE IMPLEMENTATION OF THE BPJS HEALTH PROGRAM - Ahmad Hidayat; Tuswoyo; Agista Dwiyanti (JILPR Journal Indonesia Law and Policy Review, 2022)
Based on patient visit data, the number of people who need outpatient health services through the BPJS Health program has increased since 2017. However, based on the results of a patient satisfaction survey in 2019, it appears that the health services provided are not optimal even though most patients are quite satisfied. There are still complaints that are submitted regarding the service procedure is considered complicated and long because it has to go through several administrative stages and the length of time to take care of registration. This study aims to analyze the quality of administrative and medical services at the Royal Progress International Hospital in Jakarta to patients participating in the BPJS Health program, the obstacles faced and the efforts made, using a qualitative approach with the type of case study. The results showed that the quality of health services provided included aspects of speed, pleasant service, free from errors and not all of the established procedures were met. There are still some aspects that need attention and improvement. The obstacles faced in providing health services for patients participating in the BPJS Health program come from patients who do not understand the procedures that must be passed and the incomplete requirements that must be met to obtain health services. Various efforts have been made by the management of the Royal Progress International Hospital Jakarta to overcome the obstacles faced so that health services continue to run well and are of higher quality.